2012
DOI: 10.1007/s00586-012-2217-z
|View full text |Cite
|
Sign up to set email alerts
|

Direct lateral access lumbar and thoracolumbar fusion: preliminary results

Abstract: Purpose To describe the clinical outcomes and complications in a consecutive series of extreme lateral interbody fusion cases. Methods Retrospective cohort review of 97 consecutive patients from three centers with minimum 6-month followup (mean 12 months). Functional status was evaluated by preoperative and last follow-up Oswestry Disability Index score. Leg and back pain were evaluated by visual analog scales. Complications were recorded and permanent complications and neurological impairment was actively inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
43
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 12 publications
0
43
1
Order By: Relevance
“…Rodgers's 2010 study, focusing on patients 80 years of age and older, reported no use of perioperative transfusion in MIS XLIF patients, but a 70% rate of transfusion in PLIF patients [12] . Regarding non controlled studies, Rodgers et al [13] reported a 0.2% rate of transfusion in XLIF patients, while Berjano et al [34] reported a 1% transfusion rate. Three noncontrolled studies reported on peri 999 WJO|www.wjgnet.com [14] 2007 Split process laminectomy: Marmot operation LSS 40 30 Usman et al [15] 2013…”
Section: Tlifmentioning
confidence: 99%
See 2 more Smart Citations
“…Rodgers's 2010 study, focusing on patients 80 years of age and older, reported no use of perioperative transfusion in MIS XLIF patients, but a 70% rate of transfusion in PLIF patients [12] . Regarding non controlled studies, Rodgers et al [13] reported a 0.2% rate of transfusion in XLIF patients, while Berjano et al [34] reported a 1% transfusion rate. Three noncontrolled studies reported on peri 999 WJO|www.wjgnet.com [14] 2007 Split process laminectomy: Marmot operation LSS 40 30 Usman et al [15] 2013…”
Section: Tlifmentioning
confidence: 99%
“…-0 1 -0% ---Lykissas et al [31] 295 ± 180 ---135% ---Grimm et al [32] 122 -181 -20% -3.0 -Tohmeh et al [33] ----48% ---Berjano et al [34] ----16% ---Lee et al [26] 52 ± 19 -0 [35] 73 ± 31 -< 50 -29% ---Sharma et al [36] ----70% ---Pimenta et al [25] 130 ---28% -1.4 -Ahmadian et al [37] --94 ---3.5 -Caputo et al [38] ----2 ---Malham et al [39] 84 -70 -20% ---Pimenta et al [40] 69 ± 11 -< 50 -13% ---Elowitz et al [41] ----20% 3 ---Oliveira et al [42] cutive, odd/even patient order). In Table 6 [45] polled patients on postoperative day 2, finding a VAS back of 2.2 ± 0.6 in MIS patients and 4.3 ± 0.5, a statistically significant difference (P < 0.05).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15,18,19 An extremely variable incidence of sensory (1%-75%) and motor (0%-30%) complications in the ipsilateral (nondependent) lower extremity has been documented in transpsoas clinical publications. 1,2,4,6,12,13,[20][21][22]25,29,31,32,35,36,39 Muscle and nerve injury, either independently or in combination, are suspected to play a role in these postoperative complications.…”
mentioning
confidence: 99%
“…In 2012, a retrospective study [4] on the neurological safety of the procedure (one of the hottest topics related to transpsoas surgery) was published in the Journal. Other papers have shown clinical results [5,6] for early applications, such as degenerative disc disease and degenerative spondylolisthesis or stenosis.…”
mentioning
confidence: 99%